Transplantation of human urine-derived neural progenitor cells after spinal cord injury in rats. (14th September 2020) - Liu, Aimei; Kang, Sai; Yu, Panpan; Shi, Lingling; Zhou, Libing
Highlights: Transplanted human UiPSC-NPCs mantain the potential of migration and differentation in vivo . Human UiPSC-NPCs affect the produciton of cytokines and chemokines in spinal cords. Transplanted human UiPSC-NPCs limit the lesion cavity formation after SCI. Abstract: Spinal cord injury (SCI) is a worldwide problem and transplantation of neural progenitor cells (NPCs) represents a promising treatment strategy. Urine derived induced pluripotent stem cells (UiPSCs) which enable the generation of patient-specific NPCs, provide an invaluable source of autologous cells for future therapeutic applications after SCI. However, the fate and potential contribution of transplanted human UiPSCs-derived NPCs (UiPSC-NPCs) into injured spinal cords remain largely unknown. In this study, using a rat contusive SCI model, we evaluated the survival, migration and differentiation of UiPSC-NPCs after transplantation at subacute phase. Transplanted cells survived and migrated from the site of grafting towards the lesion epicenter. More than 25 % cells survived over 4 weeks post transplantation, with a few of them differentiated into neurons and astrocytes. Cytokine and chemokine levels within the injured spinal cord tissues were measured using multiplex immunoassays to evaluate the immune response. Pro-inflammatory factors and chemokines were significantly decreased at 3 days after UiPSC-NPCs transplantation. At 7 days post transplantation, a lower level of pro-inflammatory factor IFN-γ and a higher level of pro-inflammatory IL-2 were found in UiPSC-NPCs group than in the control. Transplantation of UiPSC-NPCs showed little effect on microglia activation at the lesion epicenter. However, the number of microglia cells at 4 mm rostral to the injury site was significantly decreased. The size of lesion cavity was reduced after transplantation of UiPSC-NPCs. In conclusions, the UiPSC-NPCs transplanted at the subacute phase of SCI showed a beneficial effect on tissue repairing.